EFEK ROKOK TERHADAP KADAR FOLLICLE STIMULATING HORMONE (FSH) PADA PRIA - Hendri Devita; Vitri Yuli Afni Amran (Universitas Muhammadiyah Kudus, 2019)
Smoking gives negative impact on the reproductive health of men and women. Various hormones including sex steroid hormones may change, due to the effects of nicotine such as hypothalamus shaft - pituitary - gonads and sex steroid hormone metabolism. Nicotine can affect the central nervous system works, with the resulth that Gonadotropin Releasing Hormone (GnRH) in the hypothalamus stimulates the anterior pituitary to produce FSH and to decrease LH. Decreased FSH causes stimulation in Sertoli cells to produce decreased androgens biding protein (ABP) will also. The purpose of this study was to determine differences in the levels of FSH, LH and testosterone in heavy smokers and smokers.This study was a cross sectional analytic approach. The population were heavy smokers and non smokers at Baiturrahmah University . Consecutive sampling sampling conducted from the date of December 4, 2014 until January 13, 2015 with the samples of 50 people. FSH, LH and testosterone were checked at the Laboratory of Biochemistry, University of Andalas. Data analysis was performed by an independent t test. The results showed levels of FSH in heavy smokers and non smokers were 3.857 ± 1.493 mIU / ml and 4.977 ± 2.083 mIU / ml with p value = 0.034.From these results it can be concluded that there were significant differences in FSH mean levels in heavy smokers with the non-smokers